Differences in the motivation for seeking oral health treatment among parents of kindergarten students - Azzahra, Syahla Fatimah; Suwargiani, Anne Agustina; Muryani, Anna (Padjadjaran Journal of Dentistry, 2022)
ABSTRACTIntroduction: Motivation and the role of parents are essential in educating children on maintaining their oral health. The low parental knowledge in seeking oral health treatment will increase the prevalence of children’s oral disease. This study aimed to analyse the differences in the motivation for seeking oral health treatment among parents of kindergarten students in two kindergarten. Methods: The research was analytic with a cross-sectional technique, conducted on 109 parents taken as respondents, consisting of 54 parents of Bunda Asuh Nanda Kindergarten students and 55 parents of Mekar Arum Kindergarten students. Data collection was carried out with an online Google form questionnaire. Results: The mean intrinsic motivation range of Bunda Asuh Nanda Kindergarten and Mekar Arum Kindergarten parents was 45 to 65, while the extrinsic motivation range was 51 to 59, and the combined motivation range was 47 to 63. The Mann-Whitney test result showed a significant difference in the intrinsic and combined motivation, with a p-value of 0.0008 and 0.0073, respectively, while the extrinsic motivation showed no difference (p-value=0.2313). Conclusions: The motivation for seeking oral health treatment in parents of kindergarten students showed differences in intrinsic and combined motivation, while no difference is found in extrinsic motivation. Most of the parents in both kindergartens have rather good motivation in seeking oral health treatment for their children.Keywords: children; oral health; motivation; parents; treatment-seeking behaviour